HUBUNGAN TINGKAT PENDIDIKAN DAN PARITAS DENGAN PEMILIHAN ALAT KONTRASEPSI BAWAH KULIT PADA PASANGAN USIA SUBUR DI DESA SUKABUMI - Hana Rosiana Ulfah; Ravika Putri Kusuma Wardani; Emy Kurniawati (Jurnal Cakrawala Keperawatan, 2024)
Background: Under-skin contraceptives (AKBK) are effective and efficient hormonal contraceptives in the form of rods implanted under the skin, namely the upper arm and the protection period can reach five years. Education level and parity are factors that affect the selection of under-skin contraceptives. The level of education is one of the factors that greatly determines a person's knowledge and awareness of the importance of something, including the importance of participating in effective family planning such as under-skin contraceptives. High parity in couples of childbearing age has a tendency to use under-skin contraceptives. Research objectives: This study aims to find out whether there is a relationship between education level and parity with the selection of under-skin contraceptives in couples of childbearing age in Sukabumi village. Methods: This study was conducted using the Cross Sectional method with a population of couples of childbearing age who used contraceptives in Sukabumi Village totaling 627 people as of 2023 with a sample of 86 people through purposive sampling. The analysis test uses the Chi-Square statistical test with a confidence degree of 95% (? < 0.05). Results: From the results of the Chi - Square test , the education level of p-value 0.009 < 0.05 and the parity of p-value 0.000 < 0.05 were obtained. Conclusion: There is a relationship between education level and parity with the selection of under-skin contraceptives in couples of childbearing age in Sukabumi village. Keywords : AKBK, education level, parity